Congenital lobar emphysema presenting as recurrent pneumonia in an infant - M. D., Balaji; S., Sowmya; K. S., Naveen (International Journal of Contemporary Pediatrics, 2017)
Congenital lobar emphysema (CLE) is a developmental anomaly of the lower respiratory tract, which is characterised by hyperinflation of one or more lobes of lung. CLE is potentially reversible, though possible life threatening cause of respiratory distress in neonate. Here we present a 4 months baby who presented with respiratory distress related to CLE.